Product Bessel Distributions of the First and Second Kinds - Saralees Nadarajah (International Journal of Mathematics and Mathematical Sciences)
A new Bessel function distribution is introduced by taking the product of a Bessel function pdf of the first kind and a Bessel function pdf of the second kind. Various particular cases and expressions for moments are derived.